Comparing the effectiveness of honey with Rubus fruticosus plant powder from the Algerian farm on wounds and the resultant oxidative stress - BESNACI, Sana; BOUACHA, Mabrouka; HAMZA, Malak; HECIRI, Nour-Elhouda; KHETTACHE, Sarra; KHALFALLAH, Sarra; BABOURI, Yamine (Studia Universitatis Babeș-Bolyai Biologia, 2025)
The use of traditional remedies remains a common therapeutic option for treating burns. In this study, we investigated the healing effect of honey and Rubus fruticosus plant powder, and the combination of these two products in burn treatment and accompanied oxidative stress regulation. Over 30 days, Wistar rats with dorsal burns were divided into five groups. Burns were induced on the dorsal region, and treatments were applied topically: honey, blackberry powder, and a honey-plant powder mixture. Two groups served as controls, while treatments were administered daily. Initially, a morphological study was conducted by following the different stages of wound healing and assessing the most effective treatment. At the end of the treatment, histological sections of the wound sites were made, along with an evaluation of oxidative stress by monitoring the activity of Glutathione (GSH), Glutathione-S-Transferase (GST), Glutathione-Peroxydase (GPX), and Catalase (CAT) enzymes, biomarkers at the hepatic level. The results indicate that the natural products used are highly effective in treating burns compared to those treated with the marketed healing cream. The combination of honey and blackberry powder showed a synergistic effect in burn healing, and the histological observations support the findings from the planimetric study. The study of biomarkers shows a state of oxidative stress in the control rats through a decrease in GSH levels and an increase in the activity of hepatic GST, GPX, and CAT. In conclusion, the natural products used in our study demonstrate significant effectiveness in treating burns and oxidative stress regulation, particularly when used in combination. Article history: Received 1 October 2024; Revised 2 December 2024; Accepted 11 July 2025; Available online 20 December 2025